The consumption of fermented Chinese herbs has resulted in better intestinal health and increased resistance to Aeromonas hydrophila in juvenile largemouth bass (Micropterus salmoides) - Jiang, Li; Zhou, Xinhong; Bao, Songsong; Wu, Qiuhong; Li, Jin; Wang, Yachao; Liu, Bo (Frontiers in Marine Science, 2023)
Introduction This research aimed to assess the impact of Fermented Chinese herbs (FCHM) on the intestinal barrier, immunity, and protection against Aeromonas hydrophila (A. hydrophila) infection in largemouth bass (Micropterus salmoides). Methods Four experimental diets were formulated, including H0 (basal diet), H1, H2, and H3, which contained 1%, 3%, and 5% FCHM added to the basal diet, respectively. The fish were randomly allocated to four treatment groups, each with 3 parallel per treatment, consisting of 20 fish per replicate and were raised for 56 days. Results and discussion The experiment revealed that: compared with the control group, adding 1% FCHM significantly improved the weight gain rate (WGR) and specific growth rate (SGR) of the juvenile largemouth bass (P< 0.05). The ingestion of FCHM substantially elevated the activities of CAT, SOD, GSH-PX, APK, ACP, and LZM, and T-AOC level in the gut region of largemouth bass, while decreasing the MDA content in intestine (P< 0.05). Supplementation with FCHM enhanced the intestinal villus height and relative mRNA expression of intestinal barrier genes ZO-1, Claudin, and Occludin in juvenile largemouth bass. After injecting A.hydrophila, all groups of largemouth bass experienced mortality, but the consumption of FCHM resulted in a decrease in cumulative mortality. After infected with A.hydrophila, the antioxidant enzymes and immune enzymes activities of all test groups were enhanced compared to those before infection, and the antioxidant enzymes and immune enzymes activities of all groups were considerably higher than the control after feeding FCHM (P< 0.05). After infected with A.hydrophila, the intestinal MDA content of largemouth bass was higher compared with that before infection in all cases (P< 0.05), but after feeding FCHM, the MDA content was lower than the control (P< 0.05). Upon consuming FCHM, the mRNA relative expressions of pro-inflammatory biomarkers IL-1β, TNF-α, IL-15 and IL-8 in largemouth bass infected with A.hydrophila were decreased in comparison to the control group. In contrast, the mRNA expression of the anti-inflammatory biomarkers TGF-β and IL-10 were significantly elevated (P< 0.05). In summary, FCHM could improve the intestinal morphology, immunity, and antioxidant capacity of juvenile largemouth bass, and enhance it against A.hydrophila, with a better effect at 1% addition.